SELECTING A PUBLIC SERVICE DELIVERY ASSESSMENT TOOL FOR SOUTH AFRICA: AN APPLICATION OF THE AHP METHOD - Ajayi, Oluyomi; De Vries, Marne (The South African Journal of Industrial Engineering, 2022)
Many service delivery performance assessment (SDPA) tools exist globally that address the need to measure actual performance against pre-defined standards and to take corrective action to improve service delivery. The purpose of this paper is to guide the selection of the most appropriate SDPA tool for South Africa. Given the overwhelming civic unrest linked to public service performance levels, a solution is needed urgently. This study therefore presents a scientific approach to the process of deciding on a shortlist of off-the-shelf solutions, based on the criteria of effectiveness, project, and technical, so that a decision on the most appropriate tool for South Africa can be made on the basis of the synthesised results and a sensitivity analysis. The analytic hierarchy process (AHP) is used, and the performance journey mapping (PJM) tool has been selected on the basis of criteria and sub-criteria that were also validated for their practicality.